Washbasin Design with DFMA Approach for Covid-19 Prevention: Desain Wastafel dengan Pendekatan DFMA untuk Pencegahan Covid-19 - Iswanto; Jakaria, Ribangun B; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2022)
The Covid 19 pandemic makes the need for a washbasin in a public place to prevent the spread of the virus. However, in practice the available washbasins are still not standardized and not ergonomic. So that in this study an ergonomic washbasin design was tried using the DFMA (Design for Manufacture and Assembly) method. Because using the DFMA method aims to improve the design. Through this method, it is possible to produce products with a shorter time and the number of components that are more effective in accordance with the function but have better design quality.